Gender-Based Tax Policies: Ensuring Rights for Working Mothers and a Healthy Generation - Kusuma Wardani, Linda; Adiwarman, Adiwarman ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
This article discusses how income tax incentives can support the success of exclusive breastfeeding programs while simultaneously increasing female labor force participation in Indonesia. Using a qualitative approach based on literature studies, this research analyzes the implementation of gender-based tax policies in several countries, particularly Malaysia, and explores their relevance to Indonesia. The findings indicate that tax policies that consider the economic burden of working mothers—such as tax deductions for breastfeeding and childcare expenses, as well as tax exemptions for women returning to work after a career break—have the potential to improve family welfare and economic productivity. This policy formulation not only supports the success of exclusive breastfeeding as part of the Sustainable Development Goals (SDGs) agenda but also contributes to increasing the female labor force participation rate. However, implementing these policies faces challenges such as administrative constraints, limited workplace support facilities, and persistent gender stereotypes in society. Therefore, cross-sectoral synergy is needed in designing more inclusive and sustainable tax policies to eliminate structural barriers for working women. This study has significant theoretical and practical implications for designing a fair and gender-responsive tax system. Theoretically, it expands the understanding of how social justice principles and the recognition of reproductive labor can be integrated into fiscal theory while also highlighting the intersection between tax policy and family welfare. From a policy perspective, the findings support the need for tax reforms that provide specific deductions or incentives for working mothers and promote childcare and child health services as strategic investments for future generations. Socioeconomically, gender-sensitive tax policies have the potential to increase female labor force participation, strengthen children's rights, and reduce gender inequality within households.